Analysis of the Use of STEM and Its Elements in the Herzegovina-Neretva Canton Educational System - Medar, Amela (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
The fourth industrial revolution is gaining momentum and affects every aspect of our daily lives: the boundaries between STEM disciplines (Science, Technology, Engineering, Mathematics), as well as between STEM and non-STEM disciplines are becoming increasingly blurred. To successfully implement STEM approach to teaching, it is necessary to develop curricula based on competencies, to provide assistance and support to the teachers and curriculum creators to meet the requirements for successful STEM education in the 21st century. The aim is to identify and describe the elements that can contribute to the development of STEM competencies of students in the existing context of curricula in the Herzegovina-Neretva Canton (HNC). The paper will operationalize key concepts of STEM education, and a special segment is dedicated to the analysis of the results of the TABLA project, which should lead to improved learning outcomes for students and teachers at HNC through an innovative approach, coherent and efficient integration of teaching content.